VARIATION OF NON-CODING REGION AND CODING REGION OF 5’-TERMINAL CRNA OF POLYMERASE BASIC 1 OF AVIAN INFLUENZA VIRUS SUBTYPE H5N1 - Yuniati Kencana, Gusti Ayu; Asmara, Widya; Rangga Tabbu, Charles; Kade Mahardika, I Gusti Ngurah (Jurnal Veteriner, 2009)
The sequence of the Non-Coding Region (NCR) and Coding Region (CR) of 5’-terminal cRNA of thepolymerase basic 1 (PB1) gene as a major factor for the species adaptation of avian influenza virussubtype H5N1 (AIV H5N1) has been analysed. The information could be a virological signal for theemergence of a new strain with pandemic potential. Total RNA from twenty six (26) avian influenzasubtype H5N1 isolates were amplified using reverse-transcriptase-polymerase chain reaction (RT-PCR)with a universal forward primer for influenza virus and specifically designed backward primers. Fifteen(15) PB1 gene fragments could be amplified. RT-PCR products were sequenced and analyzed using Mega4software. The length of NCR of PB1 gene was found to be 24 bases and mostly shows conserved sequence,with an exception of Dk/Badung/2006 isolate which has C-7T substitution. A/T composition of PB1 NCRwas 54,2%, while the Dk/Badung/2006 isolate was 58,3%. Species and geographical specificity could not befound in the genetic distance, the amino acid polymorphism, as well as the phylogenetic analysis of t
Keywords: Non coding region, coding region, 5’- terminal cRNA, PB1 gene, avian influenza, H5N1, Indonesia